Evaluation of the Performance of Creative Arts Teachers of Cape Coast Metropolitan Kindergarten Schools - Ansah, Stephen Owusu (International Journal of Scientific Research and Management (IJSRM), 2018)
The purpose of the study was to evaluate the performance of creative Arts Teachers of Cape Coast Metropolitan Kindergarten Schools. The research design adopted for this study is the descriptive survey. The research design adopted for this study is the descriptive survey. Twenty-two (22) teachers and ten (10) head teachers totalling thirty-two (32) were used for the study. Questionnaire and observation were the instruments used for the study. It was found out that teachers have the necessary creative art skills and new knowledge pupils need to acquire. It was also found out that although the KG schools in the Cape Coast Metropolis have teaching and learning materials, the materials are not in suitable conditions. It was recommended that teaching and learning materials must be kept in a suitable condition.